ANALISIS WORK LIFE BALANCE DAN MOTIVASI KERJA TERHADAP EFEKTIVITAS KERJA PADA KARYAWAN GENERASI Z - Rosfitri Harum Jayanti; Dyah Cahyasari (JURNAL LENTERA BISNIS, 2026)
The changing landscape of the world of work requires organizations to understand the characteristics of the digital generation, which currently dominates the workforce and places high value on psychological well-being and flexibility. The purpose of this study is to examine the influence of work-life balance and work motivation on the work effectiveness of Generation Z employees. The study aims to examine the influence of work-life balance and work motivation on work effectiveness among Generation Z employees. The research design employs a quantitative causal approach. Data were collected through questionnaires distributed to 52 respondents, predominantly Generation Z employees selected using purposive sampling techniques. Data analysis was conducted using multiple linear regression with IBM SPSS 32 software. The partial test (t-test) results indicate that work-life balance has a positive and significant effect on work effectiveness. Similarly, work motivation also shows a positive and significant effect on work effectiveness. Simultaneously (F-test), both independent variables significantly affect work effectiveness. The coefficient of determination reveals that work-life balance and work motivation contribute 62.5% to the work effectiveness of Generation Z employees, while the remaining 37.5% is influenced by other variables outside the scope of this study. The implications of this study highlight that the integration of balanced personal life and the fulfillment of motivation are key strategies for organizations in optimizing the performance of young employees.